China's crony capitalism : the dynamics of regime decay - Pei, Minxin (2016)
"When Deng Xiaoping launched his economic reforms in the late 1970s, he vowed to build "socialism with Chinese characteristics." Three and half decades later, behind its rapid growth and glitzy façade, modernization under one-party rule has spawned a form of rapacious crony capitalism characterized by endemic corruption, an incipient kleptocracy, record income inequality, and high social tensions. This book traces the origin of China's crony capitalism to a set of incomplete reforms of property rights in the post-Tiananmen era that have decentralized the control of public property without clarifying its ownership. This combination has created an ideal environment for political and economic elites to collude and amass private wealth through systematic theft of nominally state-owned property, in particular land, natural resources, and state-owned enterprises (SOEs). Based on illuminating details from 260 well-researched cases of corruption involved multiple officials and businessmen since the early 1990s, this study investigates how collusion among elites has penetrated the vital sectors of the Chinese political and economic systems. These cases reveal a well-developed illicit market for power inside the Chinese party-state, in which bribes and official appointments are surreptitiously but routinely traded. They also document the widespread theft inside Chinese SOEs and collusion between law enforcement officials and organized crime. Above all, through its in-depth analysis of the exchange of money for favors between government officials and private businessmen, the study shines a spotlight on the dark world of crony capitalism in China - and a Leninist regime in late-stage decay."--